How does organizational culture shape the relationship between entrepreneurial orientation and the organizational performance of banks? - Al-Swidi, A.K.; Mahmood, Rosli (2011)
The complexity and turbulent business environment nowadays forced organizations to enhance their capabilities to be able to respond to all the environmental changes.As a sign of response banks, among other organizations, tried to acquire unique resources and capabilities, develop innovative and entrepreneurial culture. This argument has been justified by the increasing attention given by many researchers to examine the interaction between the Entrepreneurial Orientation (EO) and Organizational Culture (OC).Moreover, a great deal of attention has been paid to the performance implication of this interaction.This paper reviewed the literature related to the interaction between entrepreneurial orientation (EO), organizational culture (OC) and organizational performance of banks.